The influence of organizational culture, work commitment, and employee loyalty on employee performance on PT Millennium Pharmacon - Eli Delvi Yanti; Afrizal Ramadhan Siregar (International Journal of Management, Economic and Accounting, 2023)
This research aims to determine and analyze the positive and significant influence of organizational culture, organizational commitment and loyalty on employee performance at PT Millennium Pharmacon both partially and simultaneously. This research uses quantitative methods with the data analysis technique used, namely multiple linear regression. The sample in this study was 90 respondents. The results of the research show that: (1) The organizational culture variable has a calculated t value (7.753) > t table (1.66277) and a significance value of 0.000 < 0.05, which means that the organizational culture variable (X1) partially has a positive influence and significant impact on employee performance (Y) at PT Millennium Pharmacon. (2) The organizational commitment variable has a calculated t value (3.424) > t table (1.662) and a significance value of 0.001 < 0.05, which means that the organizational commitment variable (X2) partially has a positive and significant influence on performance (Y ) employees at PT Millennium Pharmacon and (3) The loyalty variable has a calculated t value (3.191) > t table (1.662) and a significance value of 0.002 < 0.05 which means that the loyalty variable (X3) partially has a positive influence and significant impact on employee performance (Y) at PT Millennium Pharmacon. (4) The variables organizational culture, organizational commitment and loyalty have a calculated F value (89.301) > F table (2.71) with a sig level of 0.000 < 0.05, which means that the variables organizational culture (X1), organizational commitment (X2) , and loyalty (X3) simultaneously have a positive and significant influence on employee performance (Y) at PT Millenium Pharmacon, (5) while the magnitude of the influence that the independent variable has on the dependent variable is 74.9%. Meanwhile, the remaining 25.1% was influenced by other factors outside this research.